The Role of Peer Support in Fostering the Spirit of Life in Patients with Human Immunodeficiency Virus - Anwar, Azmiral; Lahmuddin, Lahmuddin; Nurhanifah, Nurhanifah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Patients with Human Immunodeficiency Virus often face stigma, discrimination, and psychological pressure that causes them to lose their will to live. There have not been many studies that specifically highlight how peers can revive their will to live through therapeutic communication. This study aims to analyze the role of peers in fostering the spirit of living among Human Immunodeficiency Virus patients at a humanitarian foundation in Indonesia. This study uses a qualitative method with a case study approach that focuses on the supportive role of peers in fostering the spirit of living among people with Immunodeficiency Virus/Acquired Immunodeficiency Syndrome. Data was obtained through in-depth interviews with 12 informants, consisting of the foundation director, program manager, three peer supporters, two counselors, a doctor, and five HIV/AIDS patients, supplemented by observation and documentation of the foundation's activities. This study found that therapeutic communication conducted by peer supporters at the Medan Plus Foundation in Medan City had a significant effect on improving self-acceptance and zest for life among people living with HIV/AIDS. There are eight main roles that are carried out, namely an empathetic approach, a non-judgmental attitude, gradual communication through social media, face-to-face meetings, maintaining trust, using language appropriate to the emotional condition, providing emotional support, and therapeutic education. These findings are useful as a reference for health practitioners, social institutions, and the community to strengthen emotional support and therapeutic communication for people living with HIV/AIDS. The implications of this research emphasize the importance of the role of peer supporters in improving the quality of life of people living with HIV/AIDS.